Methods of assessment of intensity of rice tungro disease (RTD) - P. MUTHULAKSHMI, P. NARAYANASAMY and (Indian Phytopathology, 2002)
A scoring system to distinguish different intensities of disease symptoms based on the effect of disease on plant height, number of leaves showing discoloration and the presence or absence of interveinal chlorosis in the youngest emerging leaves is reported. Using the scoring system, 12 rice varieties were screened for their resistance to rice tungro disease (caused by rice tungro spherical waikavirus and rice tungro bacilliform badnavirus): 4 were highly resistant (Habiganj, DW8, ARAC 11554 and Utri Rajapan), 2 were resistant (Pankhari 203 and Gampai 30-12-15), 2 were moderately susceptible (Ponni and Whiteponni), 2 were susceptible (Co. 45 and IR20) and 2 were highly susceptible (TKM9 and TN1).